Deteksi Larva Cacing Pada Sapi dengan Pola Pemeliharaan yang Berbeda di Wilayah Kabupaten Sumedang - Iis Wili Wildan Susana; Oki Imanudin; Dini Widianingrum (Tropical Livestock Science Journal, 2024)
The aim of this research is to analyze differences in levels of digestive tract worm infections in cattle with different rearing patterns in the Sumedang Regency area. The research was carried out in January 2024 in the Paseh sub-district, Sumedang Regency. Worm larvae detection examinations were carried out at the Subang Veterinary Laboratory (B-VET), Jln. Garuda Canal, Werasari Block, Dangdeur, Subang District, Kab. Subang. The method in this research is descriptive observational carried out in the field and laboratory. The technique for collecting feces samples is carried out rectally, approximately 5 grams per cow, selecting samples based on simple random sampling. Fresh feces were put into 50 ml jars along with formalin to prevent eggs from hatching during transportation and storage. Each sample is given a label that includes the sample code and age information. After that, the samples are carried using a coolbox from the sampling location until they are examined in the laboratory. The research results showed that the prevalence pattern of worm infections in semi- intensive rearing was higher than in intensive rearing. The types of worms identified are Nematoda, Trematoda and Protozoa. Different maintenance patterns (Semi-intensive and Intensive) in Paseh District are classified as mild infections (1 – 156 epg).